Foreword - Prof. Dr. Aileen Tan Shau Hwai; Dr. Hasnuri Mat Hassan; Dr. Mahadi Mohammad; Dr. Zarul Hazrin Hashim (Tropical Life Sciences Research, 2016)
This special issue of the Tropical Life Science Research (TLSR) brings together papers presented at the 9th Regional IMT-GT UNINET Conference 2014, held at Penang, Malaysia from 3rd – 5th November 2014. The meeting was organised by the staff of School of Biological Sciences, Universiti Sains Malaysia. With the theme “Integrated Multidisciplinary & Transboundary Research for Global Transformation”, this conference provided a platform for all researchers to interact and share their research findings and ideas to foster long-term collaboration as a way forward through endeavour that stretches across multi disciplines.The three-day conference attracted over 119 participants, with 94 oral and 43 poster presentations, encompassing the fields of biodiversity, environment and conservation, biotechnology and food technology, biomedical and health sciences, pharmaceutical and natural resources, and agriculture. These topics reflect the advances in the research and knowledge of these fields. The sessions were all well supported.This conference and its selected papers are not only an outstanding example of sub-regional collaboration among scientists—in an important ecoregion of the IMT-GT countries and beyond—the resulting studies and reviews are, at the same time, a much needed and welcome contribution to the knowledge base especially in biological sciences.This special issue is a combined effort of the editors of this issue, the authors, the many referees, and the editorial assistants of TLSR who worked tirelessly and within a tight timeline. The guest editors wish to thank the enormous contribution by all the colleagues and friends. We would like to thank Universiti Sains Malaysia and the School of Biological Sciences for the continued support. It is due to the persistent effort of the team in Penerbit Universiti Sains Malaysia and the editors, that this volume is published without further delay.Guest EditorsProf. Dr. Aileen Tan Shau HwaiDr. Hasnuri Mat HassanDr. Mahadi MohammadDr. Zarul Hazrin Hashim